Specific gut microbial, biological, and psychiatric profiling related to binge eating disorders: A cross-sectional study in obese patients - Leyrolle Q; Cserjesi R; Mulders MDGH; Zamariola G; Hiel S; Gianfrancesco MA; Rodriguez J; Portheault D; Amadieu C; Leclercq S; Bindels LB; Neyrinck AM; et al. (Elsevier, 2022)
Background & aims
Binge eating disorder (BED) is a frequent eating disorder associated with obesity and co-morbidities including psychiatric pathologies, which represent a big health burden on the society.
The biological processes related to BED remain unknown. Based on psychological testing, anthropometry, clinical biology, gut microbiota analysis and metabolomic assessment, we aimed to examine the complex biological and psychiatric profile of obese patients with and without BED.
Methods
Psychological and biological characteristics (anthropometry, plasma biology, gut microbiota, blood pressure) of 101 obese subjects from the Food4Gut cohort were analysed to decipher the differences between BED and Non BED patients, classified based on the Questionnaire for Eating Disorder Diagnosis (Q-EDD). Microbial 16S rDNA sequencing and plasma non-targeted metabolomics (liquid chromatography-mass spectrometry) were performed in a subcohort of 91 and 39 patients respectively.
Results
BED subjects exhibited an impaired affect balance, deficits in inhibition and self-regulation together with marked alterations of eating behaviour (increased emotional and external eating). BED subjects displayed a lower blood pressure and hip circumference. A decrease in Akkermansia and Intestimonas as well as an increase in Bifidobacterium and Anaerostipes characterized BED subjects. Interestingly, metabolomics analysis revealed that BED subjects displayed a higher level of one food contaminants, Bisphenol A bis(2,3-dihydroxypropyl) ether (BADGE.2H(2)O) and a food derived-metabolite the Isovalerylcarnitine.
Conclusions
Non-targeted omics approaches allow to select specific microbial genera and two plasma metabolites that characterize BED obese patients. Further studies are needed to confirm their potential role as drivers or biomarkers of binge eating disorder.